(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
The importance of the research lies in the preparation of qualitative exercises in a scientific way, as researchers see that they affect the development of the ability to speed the movement response and the complex skill (V cat rotation, receiving the ball, lay-up shot) for the beginners of basketball. The objective of the research was to: Prepare qualitative exercises using auxiliary means, to identify the effect of specific exercises in developing the ability to speed the movement response and the compound skill (V cat rotation, receiving the ball, lay-up shot) for junior basketball. The researchers used the experimental approach in solving the research problem, and on the research community, the research community was identified with the (12) players of the Al Hilla Sports Club for the 2020-2021 sports season, and they were distributed into two groups equally in a random way (the draw method), and then dealt with Data using appropriate statistical methods.